Static and transient pin-by-pin simulations of a full PWR core with the extended coupled code system DYNSUB. (October 2015) - Daeubler, Miriam; Trost, Nico; Jimenez, Javier; Sanchez, Victor; Stieglitz, Robert; Macian-Juan, Rafael
Highlights: The pin-by-pin reactor simulator DYNSUB is an improved multi-physics tool. The simulation of LWR cores with pin-by-pin/sub-channel resolution is possible. DYNSUB pin-by-pin was successfully applied to the MOX/UO2 core transient benchmark. The applicability of DYNSUB pin-by-pin for LWR safety analysis proven in principle. Abstract: The evolutionary multi-physics tool developed at the Karlsruhe Institute of Technology is the homogeneous pin-by-pin reactor simulator DYNSUB, an internal coupling of the 3D neutron kinetics code DYN3D developed by Helmholtz Zentrum Dresden Rossendorf and the in-house sub-channel code SUBCHANFLOW. The ultimate goal of the on-going efforts concerning DYNSUB is to provide a cost-effective improved description of light water reactor core behavior with pin-by-pin resolution for both static and transient safety relevant scenarios. A cost-effective computer code is defined to be executable on commodity computing clusters which users/customers commonly have access to. Efforts undertaken to improve DYNSUB's numerical performance and parallelize the code system are presented in this work. Moreover, the coupled code system has been extended in terms of fuel pin level homogenization corrections and flexible mapping schemes. After optimization and extension DYNSUB is successfully applied to study the OECD/NEA and U.S. NRC PWR MOX/UO2 core transient benchmark with both fuel assembly/channel and pin level/sub-channel model resolution. Even though further improvements in terms of numerical performance and accuracy of physical models are required, the applicability of DYNSUB pin-by-pin simulations for light water reactor safety analysis is proven in principle in this work.